Influenza Virus-like Particle Containing Two Different Subtypes of Hemagglutinin Confers Protection in Mice Against Lethal Challenge With A/PR8 (H1N1) and A/HK (H3N2) Viruses - Rezaei, Farhad (Kowsar, 2013)
BACKGROUND: Preventing the seasonal or pandemic outbreak of influenza can be powerful and cost-effective. OBJECTIVES: In this study, we constructed a novel virus-like particle (VLP) platform that contains two hemagglutinin (HA) subtypes and evaluated immunogenicity of constructed VLP in mice. MATERIALS AND METHODS: This recombinant candidate vaccine model resulted in the expression of two HAs of H1N1 and H3N2 subtypes co-localized within a VLP. Following infection of insect cells with recombinant baculovirus co-expressing H1, H3 and M1 proteins, VLPs with size of 80–120 nm were self-assembled, budding, and released into the insect culture medium. The resulting VLPs which contained two different subtypes of hemagglutinin were purified by ultracentrifugation. The immunogenicity of VLPs was evaluated in mice following immunization. RESULTS: Our data showed that vaccination using VLPs elicited robust levels of serum IgG, and viral neutralizing antibodies against A/PR8 (H1N1) and A/HK (H3N2) viruses. Following challenge with lethal dose of A/PR8 (H1N1) and A/HK (H3N2, vaccinated mice were protected, displaying no sign of weight loss and mortality compared to non-vaccinated control mice. CONCLUSIONS: VLPs can serve as a promising vaccination strategy to control influenza virus.